Targeting glial cell pyroptosis and neuroinflammation in post-stroke depression: from molecular mechanisms to therapeutic strategies - Li, Xinyao; Wei, Yuanyuan; She, Yuqing; Long, Wenjuan; Zhou, Sitong; Shi, Mingqin; Wang, Zihui; Zou, Xuelian; Mao, Jianqin; Xiao, Xiangdian; Shi, Hongling; Qin, Dongdong (Frontiers in Immunology, 2025)
Post-stroke depression (PSD) represents a prevalent and debilitating sequela following cerebrovascular accidents, with its underlying pathophysiology intricately linked to neuroinflammatory processes. Emerging evidence implicates glial cell pyroptosis depending on Caspase-gasdermin D (Casp-GSDMD), orchestrated by the NLR family pyrin domain containing 3 (NLRP3) inflammasome-mediated inflammatory cascades, as a central mechanism in PSD pathogenesis. This review provides a comprehensive analysis of the molecular mechanisms governing glial cell pyroptosis and its dual role in PSD. Specifically, ischemia and hypoxia induce mitochondrial dysfunction and reactive oxygen species (ROS) accumulation, thereby promoting the release of pro-inflammatory cytokines, including IL-1β and IL-18, via the NLRP3/Caspase-1/GSDMD axis. This subsequently exacerbates neuroinflammation and disrupts the blood-brain barrier (BBB) integrity. Furthermore, aberrant activation of pyroptosis-related molecules can trigger neuronal death and impair synaptic plasticity, directly contributing to depressive symptoms. Consequently, therapeutic interventions targeting key nodes within the pyroptosis pathway, such as NLRP3, Caspase-1/4/11, and GSDMD, hold considerable promise, encompassing small molecule inhibitors, natural compounds, and combination therapies. This review synthesizes the multifaceted mechanisms of glial cell pyroptosis in PSD, highlighting the unique therapeutic potential of targeting the pyroptosis pathway to enhance post-stroke neurorepair and mitigate emotional disturbances. These findings may facilitate the identification of novel therapeutic targets and strategies for the diagnosis and management of PSD.